THE EFFECTIVENESS OF LAUGH THERAPY TO DECREASE DEPRESSION LEVEL IN THE ELDERLY AT GRIYA USILA ST. YOSEP SURABAYA AND PANTI WERDHA BHAKTI LUHUR SIDOARJO - Nurwela, Trifonia Sri; Mahajudin, Marlina S; Adiningsih, Sri (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2015)
The aging process is a natural process where an elderly experiences the changing biological, cognitive, psychological, and spiritual. Those chances influence the elderly health in both biological and psychological including the chance or mental health disorders towards an elderly which influences the quality of life such as mood disorder and depression. The managing of depression in the elderly could be done by laugh therapy. Laugh therapy is a therapy method by utilizing laugh in order to assist each person to reduce a problem in both physical disorder and mental disorder. This study aimed to determine the effectiveness of laugh therapy on the decreasing of depression level for elderly. It included quasi- experimental study was condected at Griya Usila St. Yosef and in Werdha Bhakti Luhur House in Sidoarjo by utilizing non randomized control pretest posttest design. The sample used in this research the inclusion criteria was 35 people which were divided into treatment group and control group. The treatment group was 19 people and control group was 16 people. The elderly in Griya Usila St. Yosef was as treatment group and the elderly in Panti Wedha Bhakti Luhur was as control group. Both groups performed pretest and postet at the same time to determine the level depression using by Geriatric Depression Scale/GDS. Mann Whitney Test results z = -5.105 and p = 0.000 There are significant differences in changes in the level of depression in the treated.Mann Whitney Test to test the difference in value of the Geriatric Depression Scale(GDS) z = -4.368 and p = 0.000 that was significant differences in the difference in the value of the GDS between the treated group and control group. Laughter therapy is effective in lowering the rate of depression in the elderly. The conclusion is the laugh therapy is effective in reducing the depression level in the elderly at Griya Usila St. Yosef Surabaya and Panti Werdha Luhur Sidoarjo